Ee Hui En Yayasan UMP volunteer receives Royal Education Award Pingat Jaya Cemerlang - Nadira Hana, Abdul Hamid; Nur Hartini, Mohd Hatta (2022)
KUANTAN, 6 August 2022 - Holder of a Bachelor of Engineering Technology (Pharmaceutical) with Honours degree from the Faculty of Chemical and Process Engineering Technology (FTKKP) with a CGPA of 3.89, Ee Hui En, 25, who is also a UMP volunteer was selected as the recipient of the Royal Education Award (Pingat Jaya Cemerlang) at the Universiti Malaysia Pahang (UMP) 16th Convocation Ceremony.